Influence of the number of feeding environments on the performance of bullfrog tadpoles - doi: 10.4025/actascibiolsci.v36i1.16757 (Acta Scientiarum. Biological Sciences, 2013)
Feeding is one of the major factors that influences the growth and development of animals, justifying thus the present experiment that analyzed the effect of the number of feeding environments on the performance of bullfrog tadpoles through the growth (weight and length) and performance (food remains, average feed intake, average weight gain, and feed conversion). The treatments consisted of subunits of two, four, and eight feeding environments in the experimental units at disposal for the tadpole population, and one without subdivisions, comprising a single environment, during 60 experimental days. The design was completely randomized, with four treatments and three replications. The values were tested using an analysis of variance and Duncan test (Î± = 0.05). The growth in weight and length and the indices of animal performance were influenced by the number of feeding environments, with the best results found for the treatments with four and eight environments, and the worst, for the treatment with a single environment. The increased number of feeding environments may be an alternative to improve the performance of bullfrog tadpoles.